Analisis Pengendalian Internal atas Siklus Pelaporan pada Sistem Aplikasi Keuangan Tingkat Instansi (SAKTI) - Putri, Nita Winatasari; Harahap, Siti Nurwahyuningsih (Politeknik Ganesha Medan, 2024)
This research was conducted to analyze the implementation of internal control over the financial reporting cycle at the Ministry of Foreign Affairs, especially in the year of 2022 after all the ministries are obliged to implement the Agency Level Financial Application System referred as SAKTI. This research used a case study methodology with a qualitative descriptive data analysis on a single unit analysis by using the Committee of Sponsoring Organization of the Treadway Commission Internal Control-Integrated Framework (COSO) theoretical framework adjusted to PMK.17/PMK.09/2019. The data collection in this research was obtained through interviews, documentations and observations techniques which were processed and analyzed using the content analysis method using the Nvivo12 Pro application tool. The results show that the effectiveness of internal control plays an important role in the organization to present an accurate and accountable financial reports. The manual procedures in data recapitulation and journal record in SAKTI had an impact on the occurrence of human errors which causing the need of corrections to be made in the following periods. Based on the results, it is concluded that internal control over financial reporting cycle at the Ministry of Foreign Affairs has been implemented but it is still not effective, so it needs some improvements such as the need to digitize manual procedures in data recapitulation and journal interconnection in SAKTI and also optimize monitoring activities for accurate and accountable financial reports in the future.